Silane Effects on in-Rubber Silica Dispersion and Silica Structure (aF) - A Review - Kim, Kwang-Jea (Asian Journal of Chemistry, 2013)
The degree of silica dispersion in a rubber matrix is an important issue in the rubber industry because silica agglomerates in rubber compounds are difficult to disperse compared to carbon black due to the polar characteristics of the silica surface. Considerable effort has been made to improve the degree of silica dispersion, such as the use of bifunctional organosilane, intermesh rotor type mixer, milling technique, etc. Wolff and his coworkers introduced the in-rubber filler structure (aF) for quantitative measurements of the filler structure. This paper reviews his research on the in-rubber structure of carbon black and silica and reports our recent results on silane-treated silica.